Integrated public education, fertility and human capital - Leonid V. Azarnert (Center for Economic Studies and ifo Institute (CESifo), 2011)
This article analyzes the consequences of integration in public education. I show that the flight from the integrated multicultural public schools to private education increases private educational expenditures and, as a result, decreases fertility among more affluent parents whose children flee. In contrast, among less prosperous parents, integration in public education decreases their children's human capital levels. I demonstrate that the poor, who cannot opt out, incur greater costs than the rich, who can resort to private education. I also analyze the overall society-wide effect of the integration policy and derive a condition that determines precisely whether this policy increases or decreases the average level of human capital in society.
Keywords: I20; J10; 330; public education; private education; integration; fertility; human capital; Allgemeinbildende Schule; Soziale Integration; Soziale Schicht; Privatschule; Fruchtbarkeit; Bildungsinvestition; Theorie